1997
DOI: 10.1074/jbc.272.26.16103
|View full text |Cite
|
Sign up to set email alerts
|

Ssd1p of Saccharomyces cerevisiae Associates with RNA

Abstract: The SSD1 gene has been isolated as a single copy suppressor of many mutants, such as sit4, slk1/bck1, pde2, and rpc31, in the yeast Saccharomyces cerevisiae. Ssd1p has domains showing weak but significant homology with RNase II-related proteins, Cyt4p, Dss1p, VacB, and RNase II, which are involved in the modification of RNA. We found that Ssd1p had the ability to bind RNA, preferably poly(rA), as well as single-stranded DNA. Interestingly, the most conserved domain among the RNase II-related proteins was not n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 45 publications
7
123
0
Order By: Relevance
“…It is also conceivable that Ssd1 performs additional functions in the cell independent of its phosphoCTD association. This would be consistent with the finding that Ssd1 can be found both in the nucleus and in the cytoplasm (49). Functions of Ssd1 independent of the phosphoCTD made by CTDK-I would also help to explain phenotypes displayed by various ssd1 and ctk1 mutants.…”
Section: Pcaps and Their Phosphoctd-interacting Domains (Pc-ids): Funsupporting
confidence: 87%
See 2 more Smart Citations
“…It is also conceivable that Ssd1 performs additional functions in the cell independent of its phosphoCTD association. This would be consistent with the finding that Ssd1 can be found both in the nucleus and in the cytoplasm (49). Functions of Ssd1 independent of the phosphoCTD made by CTDK-I would also help to explain phenotypes displayed by various ssd1 and ctk1 mutants.…”
Section: Pcaps and Their Phosphoctd-interacting Domains (Pc-ids): Funsupporting
confidence: 87%
“…Ssd1, a member of the ribonuclease II family of proteins ( Figure 4A), has been implicated in diverse pathways regulating cell growth and differentiation (e.g., refs [46][47][48][49][50][51][52][53][54][55][56]. It has been shown to interact genetically with many different proteins, but very little is known about its biochemistry.…”
Section: Characterization Of Pcaps (A) Identification Of the Pctd-inmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that MSL1 encodes a splicing factor and that Msl1p function is required for the effect of NST1 on salt tolerance stresses the importance of efficient RNA processing under salt stress conditions. Interestingly, the SSD1 gene, which affects lithium tolerance (see above) without significantly altering intracellular lithium accumulation (data not shown), also is able to associate with RNA (Uesono et al, 1997) and was identified as a general splicing mutant suppressor (Luukkonen and Seraphin, 1999). Finally, a novel yeast genomewide two-hybrid screen has revealed protein-protein interactions between the NST1/YNL091w gene product and Lsm4p, a Sm-like protein associated with spliceosome assembly (Fromont-Racine et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The insertion sites were located at 1317 base pairs and 2164 base pairs downstream of the start codon of the 3753-base pair open reading frame of SSD1. Because the C-terminal conserved region of Ssd1p is required for its function (Uesono et al, 1997), both transposon insertions were likely to result in loss-of-function alleles of SSD1. SSD1 is known to genetically interact with many different genes but its physiological function is not clear.…”
Section: Pag1 and Cbk1 Act In The Same Pathwaymentioning
confidence: 99%